Guyana : Staff Report for the 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2014)
The economy has experienced seven consecutive years of robust growth, buoyed by high commodity prices, foreign direct investment and expansion of private sector credit. As part of a strategy to sustain growth, reduce poverty and curtail dependence on imported oil, the authorities are pursuing the Amaila Falls Hydro-electric Project (AFHP), entailing investment of about 30 percent of GDP. However, steps by Parliament that delayed important approvals led the private sector partner to withdraw, which could delay the project while additional financing is sought. Meanwhile, public debt remains high-around 60 percent of GDP-limiting the room to finance inclusive growth.